PENGARUH MODAL INTELEKTUAL INOVASI ORIENTASI PASAR DAN ORIENTASI KEWIRAUSAHAAN TERHADAP KEUNGGULAN BERSAING UNTUK MENINGKATKAN KINERJA PEMASARAN PERUSAHAAN BATIK DI KAMPOENG BATIK LAWEYAN SURAKARTA - Istillah, Wiwik; Martono, Trisno; Riani, Asri Laksmi (Jurnal Pendidikan Insan Mandiri, 2016)
The aim of this research is to obtain: (1) direct influence of intellectual capital to competitive advantages in Kampoeng Batik Laweyan Surakarta, (2) indirect influence of intellectual capital to marketing performance of through competitive advantages in Kampoeng Batik Laweyan Surakarta, (3) direct influence innovation to competitive advantages in Kampoeng Batik Laweyan Surakarta, (4) indirect influence innovation to marketing performance of through competitive advantages in Kampoeng Batik Laweyan Surakarta, (5) direct influence market orientation to competitive advantages in Kampoeng Batik Laweyan Surakarta, (6) indirect influence market orientation to marketing performance of through competitive advantages in Kampoeng Batik Laweyan Surakarta, (7) direct influence entrepreneurial orientation to competitive advantages in Kampoeng Batik Laweyan Surakarta, (8) indirect influence entrepreneurial orientation to marketing performance of through competitive advantages in Kampoeng Batik Laweyan Surakarta, and (9) influence of competitive advantages to marketing performance in Kampoeng Batik Laweyan Surakarta. This research is a quantitative research. This research is categorized in descriptive method type survey. The population of this research is entrepreneur or worker batik in Kampoeng Batik Laweyan. The data collection was done using Proportionate Stratified Random Sampling. The data gathering technique was done using quisionaire and documentation. The hypotehsis evaluation was done using Path Analysis by SPSS 17.0 obtained by a the following result: (1) intellectual capital have effect on direct to competitive advantages, (2) intellectual capital have effect on to marketing performance indirectly through competitive advantages, (3) innovation have effect on directly to competitive advantages, (4) innovation have effect on to marketing performance indirectly through competitive advantages, (5) market orientation have effect on directly to competitive advantages, (6) market orientation have effect on to marketing performance indirectly through competitive advantages, (7) entrepreneurial orientation have effect on directly to competitive advantages, (8) entrepreneurial orientation have effect on to marketing performance indirectly through competitive advantages, and (9) competitive advantages to have effect on directly to competitive advantages. Keyword: Competitive Advantages, Marketing Performance, Kampoeng Batik Laweyan